2019
DOI: 10.31580/apss.v4i2.761
|View full text |Cite
|
Sign up to set email alerts
|

ENHANCING THE 21ST CENTURY LEARNING THROUGH THE FLIPPED CLASSROOM APPROACH: A SCIENCE TEACHER’S PERSPECTIVES

Abstract: A flip classroom is closely related to the inverted classroom that promotes learning outside the classroom (Lage et al., 2000). The main reason for the implementation of the flipped classroom is to free up the allotted learning time at school so that more engaging activities could be done (Milman, 2014). Since the flipped classroom is still at its early phase in Malaysia, there are limited studies done in this area (A. Rahman, Abdullah, Mohammed, Mohd Zaid, & Aris, 2014). This preliminary study reveals thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Despite the efforts put in by the MOE, the integration of the usage of ICT and technology in education is still limited amongst Malaysian primary educators (Wasriep & Lajium, 2019). Researchers (Nilsson & van Driel, 2010;Osman et al, 2014;Wasriep & Lajium, 2019) have reported that some veteran educators are having difficulties blending with the recent teaching technologies due to the inabilities to operate educational technology or limited technology literacy.…”
Section: Current Pedagogical Trend In Teaching Esl In Malaysiamentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the efforts put in by the MOE, the integration of the usage of ICT and technology in education is still limited amongst Malaysian primary educators (Wasriep & Lajium, 2019). Researchers (Nilsson & van Driel, 2010;Osman et al, 2014;Wasriep & Lajium, 2019) have reported that some veteran educators are having difficulties blending with the recent teaching technologies due to the inabilities to operate educational technology or limited technology literacy.…”
Section: Current Pedagogical Trend In Teaching Esl In Malaysiamentioning
confidence: 99%
“…Despite the efforts put in by the MOE, the integration of the usage of ICT and technology in education is still limited amongst Malaysian primary educators (Wasriep & Lajium, 2019). Researchers (Nilsson & van Driel, 2010;Osman et al, 2014;Wasriep & Lajium, 2019) have reported that some veteran educators are having difficulties blending with the recent teaching technologies due to the inabilities to operate educational technology or limited technology literacy. Constraints such as lack of resources, poor internet connection and limited competency in operating educational technology are reported to be some of the limiting factors in implementing and integrating technology and ICT in teaching and learning processes (Osman et al, 2014).…”
Section: Current Pedagogical Trend In Teaching Esl In Malaysiamentioning
confidence: 99%
See 2 more Smart Citations